A Qualitative Pilot Study of Spirituality in Long-term Recovery in Acquired Brain Injury. (June 2019) - Gillespie, Elena
Increased spirituality occurring after acquired brain injury is a part of post traumatic growth (PTG). Participants were asked about their spirituality, and their responses were analyzed. Eighty-one percent exhibited a moderate spiritual impact on their recovery. Studies suggest that patients' spiritual needs are not being met, and chaplains are being underutilized. Trust and a sense of presence are essential to encouraging PTG, and, by fully utilizing the skills of our chaplain colleagues, could improve PTG.